Pengaruh Citra Merek dan Word of Mouth terhadap Keputusan Pembelian pada Bakso Aci Mutia di Bandar Lampung - Astabela Saputri; Habiburahman Habiburahman (Universitas Diponegoro, 2023)
The researcher's interest in the food industry business led to the conduct of this study. Humans are obligated to consume and spend food on a daily basis because food is a fundamental need. At Bakso Aci Mutia in Bandar Lampung, the purpose of this study was to determine how brand image and word-of-mouth influence purchasing decisions. The quantitative descriptive research includes this study. This study's population consisted of 30 individuals who were customers of Bakso aci Mutia in Bandar Lampung. This study employs multiple linear regression analysis for its analysis. Aci Mutia Meatballs in Bandar Lampung's purchasing decisions were influenced in part by the brand's image, as evidenced by tcount > ttable or 2.055 > 2.052 with a 0,05 significance level. Word-of-mouth influence on Aci Mutia Meatballs purchases in Bandar Lampung can be seen in part from tcount > ttable or 4.118 > 2.052, both of which have significant values of 0,00, From Fcount > Ftable or 25.734 > 3.34, a significant value of 0,000 can be seen that Aci Mutia Meatballs consumers in Bandar Lampung are influenced by the brand's reputation.Riset ini dilaksanakan dari ketertarikan pengkaji pada dunia usaha dibidang makanan. Makanan ialah bahan dasar yang mesti dicukupi orang, ini menunjukan tiap hari orang pasti mengonsumsi dan menghabiskan makanan. Riset ini dilaksanakan dengan tujuan diketahui pengaruh imaji brand dan word of mouth pada putusan pemesananBakso Aci Mutia di Bandar Lampung. Riset ini masuk ke pada riset deskriptif kuantitatif. Populasi pada riset ini ialah pembeli Bakso aci Mutia di Bandar Lampung dan total sampel sejumlah 30 orang. Analisis pada riset ini memakai analisis regresi linier berganda. Hasil riset memperlihatkan jika ada Ada pengaruh citra brand pada putusan pemesanan Bakso Aci Mutia di Bandar Lampung dengan parsial terlihat pada thitung > ttabel atau 2,055 > 2,052 Dengan nilai substansial 0,05. Ada pengaruh word of mouth pada putusan pemesanan Bakso Aci Mutia di Bandar Lampung dengan parsial terlihat pada thitung > ttabel atau 4,118 > 2,052 dengan nilai substansial 0,00, Ada pengaruh imaji brand dan word of mouth pada putusan pemesananBakso Aci Mutia di Bandar Lampung dengan simultan terlihat pada Fhitung > Ftabel atau 25,734 > 3,34 dengan nilai substansial 0,000.